My Malay identity : the moderating role of identity definition on the relationship between Identity enactment and collective identification/nonacceptance - Afiq A'Azman (Nanyang Technological University, 2020)
Previous studies have shown that one’s enactment of their collective ingroup’s norms would lead to stronger identification with that collective ingroup. However, racially Malay Singaporeans who seem to enact ‘Malay’ norms do not all identify with their Malay ethnic identity. We propose that one’s personal definition of the Malay ethnic identity would moderate the above relationship. Further, we proposed that the interaction between personal definition and enactment would extend to affect one’s judgement of deviant Malay targets. However, our results did not support our hypotheses. One’s enactment of the Malay ethnic identity affected collective identification with the Malay ethnic identity, regardless of their personal definitions. In addition, the effects participants’ personal definitions had on their evaluations of other Malay targets were consistent with our hypothesis for some components of the Malay ethnic identity. We discussed the implications of our results, as well as the reasons behind the trends we see in the racially Malay Singaporean population. Limitations and future directions of our study were also addressed.